Analisis Perilaku Penelusuran Informasi Mahasiswa Ilmu Perpustakaan UIN Sumatera Utara Dalam Menyelesaikan Skripsi - Futri Indah Sari; Putri Septiani; Vivi Mauliza; Murni Pranasari; Franindya Purwaningtyas (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
This study is entitled "Analysis of Information Searching Behavior of Library Science Students at UIN North Sumatra in Completing Undergraduate Thesis". The purpose of this study was to find out how the behavior of information retrieval of library science students in completing their undergraduate thesis at UIN Sumatra Utara. In addition, the research aims to find out what are the information needs of librarian science students at UIN North Sumatra. The research method used is a qualitative research method with a case study type of research. The subjects in this study were individuals who were library science students at UIN North Sumatra who were preparing their thesis. Then the object of this research is information retrieval behavior of library science students at UIN North Sumatra in completing their undergraduate thesis according to David Ellis. The results of this study indicate that the information needs of library science students at UIN North Sumatra, such as the subject needed is their field of study, namely the development of library science. Sources of information needed in the form of documents in the form of books and internet sources. While non-documentary sources are in the form of results of discussions in activities held by students majoring in library science. Keywords: information searching behavior; library science, undergraduate thesis